Forward Discount Bias: Is it an Exchange Risk Premium? - Froot, Kenneth A.; Frankel, Jeffrey A. (Quarterly Journal of Economics, 1989)
A common finding is that the forward discount is a biased predictor of future exchange rate changes. We use survey data on exchange rate expectations to decompose the bias into portions attributable to the risk premium and expectational errors. None of the bias in our sample reflects the risk premium. We also reject the claim that the risk premium is more variable than expected depreciation. Investors would do better if they reduced fractionally the magnitude of expected depreciation. This is the same result that many authors have found with forward market data, but now it cannot be attributed to risk.